Innovations in marketing of deposit services - T.A. Vasylieva; I.V. Didenko (Marketing i Menedžment Innovacij, 2016)
The aim of the article is recent studies of global trends in marketing of innovative deposit services. The results of the analysis. Summing up the general, it should be noted that, according to our goal, we systematized the theoretical basis of innovation in marketing services and deposit rated their performance justified the specific marketing innovation support domestic banks in the deposit market. Conclusions and directions of further researches. Deposit market is an important resource base for the banking sector of any country. Increased competition there between financial institutions in the post-crisis period is an incentive to find and implement various marketing innovation in deposit services that would help attract additional financial resources. Today, many analysts have focused on the fact that any further activities on the deposit market, including marketing, must take account of three important factors: 1. «Online competition». In this case it means the access to the financial market in order to attract temporarily free funds of non-banking institutions (insurance brokerage companies, world leaders providing IT services). These institutions are deploying a fierce fight for every customer, using global information space – the Internet. Given all modern premise, it planned to expand the presence of such companies in the online space with lucrative offers favorable interest rates on deposits with new loyalty programs relative to individual customer needs. 2. Shortage of alternatives to ensure liquidity. Since banks are limited in their ability to write off loans from their balance through exercise securitization and financing transactions in the wholesale financial markets, as they continue to feel the need to attract customer funds. This, in turn, will contribute to increased competition in the struggle for each new customer and promote the development of innovation in marketing deposit services. 3. Presence of non-national sources of funding. This is a problem, for example, for the US banking sector, where more than 18% of total deposits up foreign deposits. The desire of foreigners have deposits in the US significantly affect the liquidity of the banking system. In Ukraine we have a different situation, because the share of deposits in the national currency is more than half of all deposits of depositors in the last ten years (with the exception of the second quarter of 2015) Thus, the development of innovation in marketing services deposit has broad prospects and future needs as much attention on the part of banking and non-banking sectors.